Efficacy of Draksadi Phantam in Generalized Anxiety Disorder- An Uncontrolled Clinical Trial (International Journal of Ayurveda and Pharma Research, 2022)
Anxiety disorders are one of the most prevalent class of mental disorders in the general population. Generalized anxiety disorder (GAD) is a common anxiety disorder that comprises continuous and long-lasting worrying, tension, which making normal life problematic and relaxation impossibleThe prevalence rate of GAD disorder is increasing constantly in modern era. Though many different types of modern medications used currently to treat anxiety disorders provide temporary relief, they come with various side effects, Drug dependence and safety concerns. In Ayurveda the symptoms of this disease show resemblance with the condition. Cittodvega (excited state of mind) which is one among the Manovikara in Ayurveda caused by dysfunction of increased Vata and Pitta dosha.The present study was conducted as an Uncontrolled clinical trial to study the Efficacy of Drakshadi Phantam in 38 diagnosed participants of Generalized Anxiety Disorder with the age group 20–50 were administered with 100ml of Drakshadi Phantam twice daily before food continuously for a period of 45 days.Five assessments were done staring from 0th day of treatment to 60 the day of the study with a gap of 15 days, using Hamilton anxiety rating scale and Rajas Tams rating scale. The assessment scores of different intervals were statistically analysed using RM ANOVA. Effect of the therapy were statistically analysed in each domain of HAM – A rating scale in different intervals of the study. The therapy was found statistically significant in reducing the symptoms of GAD in all the 14 domains of the HAM- A Rating scale.              Based on results it has been concluded that Drakshadi Phantam has statistically significant effect in reducing the symptoms of all the 14 domains of Hamilton anxiety rating scale and reducing the Rajasika and Tamasika qualities of the study participants.